Workshop on land markets & rural poverty (2004. Aug 10- 11: Musoorie ) (Mussoorie, 2005)
The Centre for Rural Studies (formerly Land Reforms Unit) of the Lal Bahadur Shastri National Academy of Administration was set up in the year 1989 by the Ministry of Rural Development, Government of India, with a multifaceted agenda that included among others, the concurrent evaluation of the ever-unfolding ground realities pertaining to the implementation of the Land Reforms and Poverty Alleviation Programmes in India. Sensitizing the officer trainees of the Indian Administrative Service in the process of evaluating of land reforms and poverty alleviation programmes by exposing them to the ground realities; setting up a forum for regular exchange of views on land reforms and poverty alleviation between academicians, administrators, activists and concerned citizens and creating awareness amongst the public about the various programmes initiated by the government of India through non-governmental organisations are also important objectives of the Centre for Rural Studies. A large number of books, reports related to land reforms, poverty alleviation programmes, rural Socio-economic problems etc. published both externally and internally bear testimony to the excellent research quality of the Centre.
Keywords: Rural poverty